Multi-objective time-energy-impact optimization for robotic excavator trajectory planning - Feng, Hao; Jiang, Jinye; Ding, Nan; Shen, Fangping; Yin, Chenbo; Cao, Donghui; Li, Chunbiao; Liu, Tao; Xie, Jiaxue (Automation in construction, 2023)
Single-objective optimal trajectory cannot adapt to the complex requirements of excavator construction. A comprehensive optimal trajectory planning method is proposed to optimize the working time, energy consumption, and operational impact of robotic excavators. Without fusing any performance indexes, a normalized multi-objective function and an improved particle swarm optimization algorithm are established to achieve a comprehensive optimization of multiple objectives, while considering joint angle, velocity, acceleration, and quadratic acceleration constraints. Typical deep pit excavation simulation and experimental results show that the multi-objective optimization method is feasible, can balance multi-objective constraints, and can avoid falling into extremely long working times or large impacts. This method offers a more efficient and effective solution for multi-objective trajectory planning and provides a method for planning excavation trajectories based on different operating scenarios and objectives. •Working time, energy consumption and operation impact are considered in trajectory planning.•A normalized multi-objective function is established to achieve a comprehensive optimization.•An improved particle swarm optimization algorithm is proposed to obtain the optimal solution.•Effectiveness of the trajectory planning method is validated by simulations and experiments.•The multi-objective optimization method can meet the actual construction requirements.